The Clinical Drug Ebselen Attenuates Inflammation and Promotes Microbiome Recovery in Mice after Antibiotic Treatment for CDI - Megan Garland; Andrew J. Hryckowian; Martina Tholen; Kristina Oresic Bender; William W. Van Treuren; Sebastian Loscher; Justin L. Sonnenburg; Matthew Bogyo (Cell Reports Medicine, 2020)
Summary: Clostridium difficile infection (CDI) is an enteric bacterial disease that is increasing in prevalence worldwide. C. difficile capitalizes on gut inflammation and microbiome dysbiosis to establish infection, with symptoms ranging from watery diarrhea to toxic megacolon. We reported that the safe-in-human clinical drug ebselen (ClinicalTrials.gov: NCT03013400, NCT01452607, NCT00762671, and NCT02603081) has biochemical, cell-based, and in vivo efficacy against the toxins of C. difficile. Here, we show that ebselen treatment reduces recurrence rates and decreases colitis in a hamster model of relapsing CDI. Furthermore, ebselen treatment does not alter microbiome diversity and promotes recovery back to that of healthy controls after antibiotic-induced dysbiosis in healthy and C. difficile-infected mice. This increased microbiome recovery upon ebselen treatment correlates with a decrease in host-derived inflammatory markers, suggesting that the anti-inflammatory properties of ebselen, combined with its anti-toxin function, help to mitigate the major clinical challenges of CDI, including recurrence, microbial dysbiosis, and colitis.